Parameter study of hopping mechanism for one legged crank-type hopping robot - Abdul Rahim, Nurul Hafizah (2015)
Hopping is a desirable locomotion for a mobile robot particularly to move in unstructured environment. One of the common mechanisms for realizing the hopping locomotion is by using crank type mechanism. However the behaviour of the crank mechanism in terms of hopping performance is unknown. It is hypothesized that hopping performance of crank type hopping robot is influenced by three mechanical parameters which are crank length, spring coefficient and mass of robot. Thus the objectives of the research is to model the behaviour of crank type hopping robot particularly in terms of the effects of mechanical parameters (i.e. spring coefficient, mass and crank length) of the hopping robot towards its hopping performance, to design and simulate one legged hopping robot using Matlab software and finally to validate the simulation with experiments. The simulation and experimentation works were done by setting one of the mechanical parameters as constant value while the other two parameters were set as variable parameters. The step was repeated by changing each of the mechanical parameters as a constant while the other two are variables and vice versa. For experimentation purposes, a one legged hopping robot was developed. In the experiment, the hopping height was measured by using a calibrated Infrared Ranging (IR) sensor. The result shows that the equation of behaviour for the crank type hopping robot performance is true for a certain region as long as the upward force (stored energy in spring) can counter the downward force (force from mass).